Approaching ultimate intrinsic specific absorption rate in radiofrequency shimming using high‐permittivity materials at 7 Tesla. Issue 1 (28th November 2017) - Haemer, Gillian G.; Vaidya, Manushka; Collins, Christopher M.; Sodickson, Daniel K.; Wiggins, Graham C.; Lattanzi, Riccardo
Abstract : Purpose: The aim of this study was to evaluate the effect of integrated high‐permittivity materials (HPMs) on excitation homogeneity and global specific absorption rate (SAR) for transmit arrays at 7T. Methods: A rapid electrodynamic simulation framework was used to calculate L‐curves associated with excitation of a uniform 2D profile in a dielectric sphere. We used ultimate intrinsic SAR as an absolute performance reference to compare different transmit arrays in the presence and absence of a layer of HPM. We investigated the optimal permittivity for the HPM as a function of its thickness, the sample size, and the number of array elements. Results: Adding a layer of HPM can improve the performance of a 24‐element array to match that of a 48‐element array without HPM, whereas a 48‐element array with HPM can perform as well as a 64‐element array without HPM. Optimal relative permittivity values changed based on sample and coil geometry, but were always within a range obtainable with readily available materials (εr = 100–200). Conclusion: Integration of HPMs could be a practical method to improve RF shimming performance, alternative to increasing the number of coils. The proposed simulation framework could be used to explore the design of novel transmit arrays for head imaging at ultra‐high field strength. Magn Reson Med 80:391–399, 2018. © 2017 International Society for Magnetic Resonance in Medicine.